Reproductive biology of Psomophis genimaculatus (Boettger 1885) (Serpentes: Dipsadidae) from Brazil - Mori, Kelvin y.; Ferracini, CECiLIA M.; Piatti, Liliana [UNESP]; Cabral, Hugo; Ferreira, V. A. N. D. A. LuCIA (Acad Brasileira De Ciencias, 2025)
Although the geographic distribution, phylogeny and natural history of Psomophis genimaculatus, a snake that inhabits diverse environments, such as the Chiquitana Forest, Cerrado, Pantanal, and Chaco, have been investigated in several studies, reproductive biology assessments are still lacking for this species. In this sense, this research investigated sexual dimorphism, sexual maturity, and reproductive cycle of P. genimaculatus, specimens from Brazil. Sexually reproductive females display longer body lengths, while males possess longer tails, although similar head lengths and widths are noted males and females. The female reproductive cycle exhibits a prolonged seasonal pattern, with secondary vitellogenesis taking place from September to June and oviductional eggs appearing between July and September. Follicular length, however, was not correlated to seasonality. Fecundity was not associated to body length but was closely aligned with potential fecundity. Histological assessments indicate secondary vitellogenesis beginning at follicle length of 7.6 mm. Ductus deferens and testicular volume in males are not influenced by body size or season. A spermatogenesis peak is noted in early autumn, with residual activity observed throughout winter. This study contributes with novel data on the reproductive biology of P. genimaculatus, aiding in this species conservation efforts.
Keywords: sexual dimorphism; reproduction; reproductive cycles; sexual maturity; snakes